Stochastic Integrals in Discounting Proactive Operations - Artikis, Constantinos T.; Artikis, Panagiotis T. (Journal of Informatics and Mathematical Sciences, 2021)
Proactivity constitutes a structural factor of decision making in many practical disciplines. It is generally adopted that stochastic discounting models substantially contribute to the development and implementation of proactive operations. The paper concentrates on the formulation of a stochastic discounting model by incorporating a stochastic integral and a positive random variable. Moreover, the paper provides interpretation of the stochastic discounting model in proactive environments.